1990
DOI: 10.1002/srin.199000293
|View full text |Cite
|
Sign up to set email alerts
|

Systematische Gefügeuntersuchungen am martensitaushärtenden Stahl X 2 NiCoMo 13 15 10

Abstract: An dem als höchstfest bekannten martensitaushärtenden Stahl X 2 NiCoMo 13 15 10 wurden die Ausscheidungs‐ und Umwandlungsvorgänge untersucht. Neben der Licht‐ und Rasterelektronenmikroskopie kam dabei vor allem der Transmissionselektronenmikroskopie die entscheidende Bedeutung zu. Der Einfluß verschiedener Wärmebehandlungen auf das Gefüge wurde durch die Messung der Härte, durch Röntgenbeugung, durch Röntgenmikroanalyse und durch dilatometrische Untersuchungen verfolgt. Die ermittelten Ergebnisse wurden zur He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…It is worth mentioning that the YS of 400 ksi (2760 MPa) seems to represent an upper boundary for the maraging steels with 18%Ni 23 and that the lower limit for the 13%Ni-15%Co-Mo-Ti 12,13,24 maraging steels. The characteristics and particularities of the precipitation hardening of these new ultra-high-strength maraging steels have been studied with the help of transmission electron microscopy 12,24,26,27 and have shown that after aging the reiterated presence of three types of nanometric sized precipitates: (Ni,Fe) 3 (Mo,Ti); μ-(Fe,Co) 7 Mo 6 and the Laves phase (Fe,Co) 2 (Mo,Ti). On the other hand, several characteristics of the phase transformations and the hardening mechanisms acting in this new class of maraging steels require complementary and more detailed studies.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is worth mentioning that the YS of 400 ksi (2760 MPa) seems to represent an upper boundary for the maraging steels with 18%Ni 23 and that the lower limit for the 13%Ni-15%Co-Mo-Ti 12,13,24 maraging steels. The characteristics and particularities of the precipitation hardening of these new ultra-high-strength maraging steels have been studied with the help of transmission electron microscopy 12,24,26,27 and have shown that after aging the reiterated presence of three types of nanometric sized precipitates: (Ni,Fe) 3 (Mo,Ti); μ-(Fe,Co) 7 Mo 6 and the Laves phase (Fe,Co) 2 (Mo,Ti). On the other hand, several characteristics of the phase transformations and the hardening mechanisms acting in this new class of maraging steels require complementary and more detailed studies.…”
Section: Introductionmentioning
confidence: 95%
“…With the passing years, thoughts were to increase even more the strength of maraging steels. The base composition should be modified deriving 12,24,25 maraging steels with a YS in the order of 3 GPa, using the Fe-13%Ni-15%Co-10%Mo-Ti base composition. This new class of steels, commercially available since the '80s, became known popularly as maraging 400 and 450 steels.…”
Section: Introductionmentioning
confidence: 99%
“…Our study was about 13Ni maraging steel, an ultra-high-strength maraging Metals 2023, 13,1929 2 of 13 steel with a base composition of Fe-13Ni-15Co-10Mo-1Ti (wt.%), also known as maraging 400, and it can achieve a yield strength of 3 GPa (as reported in the literature) [1,[6][7][8][9]. The primary approach used to achieve these high mechanical strength values in 13Ni maraging steels is the increase in the volume fraction of precipitates, thereby enhancing the hardening effect through higher molybdenum and titanium contents in the steel [3,4,[9][10][11][12][13][14][15]. Molybdenum directly participates in the formation of precipitates, while cobalt synergistically reduces the solubility of molybdenum in the matrix [4,16,17].…”
Section: Introductionmentioning
confidence: 98%
“…The most conventional and widely used commercially is the 18Ni maraging steel, which consists of Fe-18Ni- (8)(9)Co- (3)(4)(5)Mo-(<1)Ti (wt.%) and has a yield strength of approximately 1.7 GPa. Our study was about 13Ni maraging steel, an ultra-high-strength maraging Metals 2023, 13,1929 2 of 13 steel with a base composition of Fe-13Ni-15Co-10Mo-1Ti (wt.%), also known as maraging 400, and it can achieve a yield strength of 3 GPa (as reported in the literature) [1,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation